COVID-19 Pandemic and Increased Teenage Pregnancy in Uganda - Kiconco, Milliam (Advances in Social Sciences Research Journal, 2021)
ABSTRACT In writing this paper, secondary review methodology has been used to explore the link between COVID-19 pandemic and increased teenage pregnancy in Uganda. Data from journal articles, text books, media outlets, government documents and Non-Governmental Organizations reports have been used in coming up with this paper. The paper begins with the general discussion of teenage pregnancy with emphasis on its negative implications on teenage girls and the reasons young girls get pregnant. This is followed by the discussion about teenage pregnancy in Uganda. This part has shown that before the advent of COVID-19 pandemic, Uganda was considered one of the countries with the highest rates of teenage pregnancy in Sub Saharan Africa. Then is a discussion on how past disasters like Ebola were also associated with an increase in teenage pregnancy. This connects to the discussion on how COVID-19 pandemic is similar to earlier disasters in causing an increase in teenage pregnancy. The increase in teenage pregnancy is attributed to preventive measures such as school closures and movement restrictions that have made girls more vulnerable to sexual advances from the perpetrators. This part is followed by the discussion on how teenage pregnancy has been amplified by COVID-19 pandemic in Uganda, Finally, the paper has recommended a multi-sectoral approach to addressing teenage pregnancy and the need for incorporating teenage pregnancy in the future plans aimed at addressing pandemics and epidemics.